2010
DOI: 10.1021/jp100929n
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Plasticity in an HIV-1 Antibody Epitope

Abstract: The structure of a short fragment of the human HIV-1 membrane glycoprotein gp41 has been examined using a combination of parallel tempering molecular dynamics (PTMD) and far UV circular dichroism spectroscopy. The aim is to resolve conflicting reports on the solution state conformational bias in this membrane proximal domain spanning the epitope for the 2F5 monoclonal antibody. We conclude that gp41(659-671) exhibits conformational plasticity in which competing folding propensities are present and can be influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 45 publications
3
29
1
Order By: Relevance
“…Thus, the region has been variously described as ahelix [16], 3 10 helix [17], type I or extended -turn [18], a flexible region that adapts to its environment [19], or even largely disordered in solution [18,20,21]. Coutant and coworkers [22], and more recently, Tulip et al [23] revealed that the structure of the N-terminus of the MPER depends strongly on the local microenvironment (i.e. pH-value, percentage of trifluroethanol).…”
Section: Structural Studies Of the Mper In Solu-tionmentioning
confidence: 99%
“…Thus, the region has been variously described as ahelix [16], 3 10 helix [17], type I or extended -turn [18], a flexible region that adapts to its environment [19], or even largely disordered in solution [18,20,21]. Coutant and coworkers [22], and more recently, Tulip et al [23] revealed that the structure of the N-terminus of the MPER depends strongly on the local microenvironment (i.e. pH-value, percentage of trifluroethanol).…”
Section: Structural Studies Of the Mper In Solu-tionmentioning
confidence: 99%
“…Recent years have witnessed sustained and intense research efforts into proteins and peptides, using a combination of experimental [1][2][3], theoretical [4][5][6] and computational methods [7][8][9][10]. There are several reasons for this interest: firstly, peptides, as the building blocks of proteins are of fundamental biological importance -successfully understanding the biological physics of these molecules will provide a major advance in our biological understanding.…”
mentioning
confidence: 99%
“…In all systems, one major basin was found. Although the current simulations could only determine the relative stabilities of the a-and 3 10 -helical states and could not be used to assess stabilities of other possible states (like b-sheets, coils, or turns), it is clear that in agreement with other findings, [15,23] the 3 10 -helical state is highly disfavored. In CHARMM, the basin was near 100% a-helical, whereas in AMBER the basin was between 80 and 90% a-helical for the lower P values and about 70% ahelical for higher P. In AMBER, residue 10 had a significantly lower probability for the a-helical state (between 20 and 50%) than the other residues; in CHARMM, all residues were equally probable to be a-helical (each between 70 and 90%).…”
Section: Resultsmentioning
confidence: 81%
“…The 3 10 -helix is also right-handed and characterized by a radius of 1.9 Å and pitch of 6.0 Å, formed by backbone hydrogen bonds between residues i and i þ 3. [11] Free energy differences between peptide helical states have been obtained from long unbiased MD simulations, [12][13][14] temperature replica exchange simulations, [15,16] umbrella sampling simulations along the C a end-toend distance, [17] constrained (u, U) backbone dihedral angle simulations, [18] and enveloping distribution sampling of the a, 3 10 , and p end states. [3] Short 3 10 -helices are common, constituting about 4% of all protein residues, [4,5] but the p-helix is rare.…”
Section: Introductionmentioning
confidence: 99%